PROGRESSIVE HEART FAILURE - Hozhiev Botir Bahtiyorovich (Web of Journals Publishing, 2024)
The article presents the problems of progressive heart failure (PHF) and despite significant, it would not be an exaggeration to say revolutionary, achievements in clinical pharmacology, cardiac surgery and implantation arrhythmology, the number of patients with chronic heart failure (CHF) is not decreasing in many countries, and in some, for example, in Uzbekistan, it is increasing. At the same time, unfortunately, the immediate and long-term results of the so-called optimal CHF therapy are often disappointing for both the patient and the doctor. In 2007 Experts from the Association of Heart Failure of the European Society of Cardiology have proposed the term PHF to refer to CHF, in which optimal drug therapy, as well as cardiac resynchronization therapy, are not effective. The article discusses the issues of terminology, diagnosis, prognostic stratification and routing of patients with PHF, as well as short- and long-term treatment strategies for these patients.
Keywords: progressive heart failure, definition, indicators, prognostic stratification, clinical markers, biomarkers, heart transplantation.